DNMT1 modulates interneuron morphology by regulating Pak6 expression through crosstalk with histone modifications. Issue 5 (4th May 2018) - Symmank, Judit; Bayer, Cathrin; Schmidt, Christiane; Hahn, Anne; Pensold, Daniel; Zimmer-Bensch, Geraldine
ABSTRACT: Epigenetic mechanisms of gene regulation, including DNA methylation and histone modifications, call increasing attention in the context of development and human health. Thereby, interactions between DNA methylating enzymes and histone modifications tremendously multiply the spectrum of potential regulatory functions. Epigenetic networks are critically involved in the establishment and functionality of neuronal circuits that are composed of gamma-aminobutyric acid (GABA)-positive inhibitory interneurons and excitatory principal neurons in the cerebral cortex. We recently reported a crucial role of the DNA methyltransferase 1 (DNMT1) during the migration of immature POA-derived cortical interneurons by promoting the migratory morphology through repression of Pak6 . However, the DNMT1-dependent regulation of Pak6 expression appeared to occur independently of direct DNA methylation. Here, we show that in addition to its DNA methylating activity, DNMT1 can act on gene transcription by modulating permissive H3K4 and repressive H3K27 trimethylation in developing inhibitory interneurons, similar to what was found in other cell types. In particular, the transcriptional control of Pak6, interactions of DNMT1 with the Polycomb-repressor complex 2 (PCR2) core enzyme EZH2, mediating repressive H3K27 trimethylations at regulatory regions of the Pak6 gene locus. Similar to what was observed upon Dnmt1 depletion, inhibition of EZH2 caused elevated Pak6 expression levels accompanied by increased morphological complexity, which was rescued by siRNA-mediated downregulation of Pak6 expression. Together, our data emphasise the relevance of DNMT1-dependent crosstalk with histone tail methylation for transcriptional control of genes like Pak6 required for proper cortical interneuron migration.